THE USE OF COMMUNICATIVE LANGUAGE TEACHING (CLT) IN TEACHING SPEAKING RECOUNT TEXTS TO THE EIGHTH GRADERS OF SMPN 28 SURABAYA (RETAIN, 2015)
Abstract Speaking is the way to communicate with other people in order to deliver creative ideas orally (Brown, 2004). Eventhough in speaking class students are demanded to keep on speaking, there are still some who stay passive. Through the use of Communicative Language Teaching (CLT), students are driven to work in pairs by sharing and finding information, delivering their ideas freely, helping to check their partner’s tasks, and receiving the feedback. This research is descriptive qualitative aiming to describe the implementation of Communicative Language Teaching (CLT) in teaching speaking recount texts to the eighth graders of SMPN 28 Surabaya and the students’ speaking performances by focusing on their fluency. The result reveals that the implementation of CLT was in line with the procedures in doing the activities modified from Richard (2006). They are mechanical practice, meaningful practice, communication practice, and feed back. From the students’ speaking performances, it can be seen that there were various levels of the students’ fluency ranging from poor to excellent. In conclusion, CLT could be implemented in teaching speaking to make the students keep practicing and help them deliver their ideas confidently. Keywords: Speaking, Teaching speaking, Recount Texts, CLT, The Eighth Grade Students. Berbicara merupakan alat untuk berkmunikasi dengan orang lain yang bertujuan untuk menyampaikan ide kreatif secara lisan. Faktanya, banyak siswa yang pasif dalam berbicara bahasa asing. Dalam pengajaran berbicara, kefasihan diperlukan untuk memaksa siswa aktif dalam berbicara di dalam kelas and meminta mereka untuk terus berbicara. Melalui Communicative Language Teaching (CLT) siswa dituntut untuk bekerja bersama pasangan dengan berbagi dan mencari informasi satu sama lain, mempunyai pilihan untuk menyampaikan ide mereka secara bebas dengan menggunakan bahasa sendiri, membantu dan mengkoreksi pekerjaan pasangan, dan mendapat umpan balik. Penelitian ini menggunakan deskripsi kualitatif untuk mendiskripsikan penenerapan Communicative Language Teaching (CLT) di dalam mengajjar berbicara teks recount untuk siswa kelas delapan SMPN 28 Surabaya dan penampilan berbicara siswa dengan focus pada kefasihan berbicara mereka. Hasil dari penelitian menjelaskan bahwa guru mengikuti prosedur dalam melakukan aktifitas yang diadaptasi dari Richard (2006). Procedure tersebut adalah latihan dasar berbicara, latihan , latihan berkomunikasi, dan umpan balik. Berdasarkan hasil dari penampilan berbicara siswa, terlihat bahwa terdapat bermacam-macam hasil dari kefasihan siswa dalam berbicara. Dapat disimpulkan bahwa “CLT” dapat diterpakan dalam mengajar speaking teks recount untuk membuat siswa melatih berbicara mereka secara terus menerus dalam membantu mereka berbicara untuk menyampaikan ide mereka secara percaya diri dalam speaking.